Inuit shamanism and christianity: transitions and transformations in the twentieth century - Laugrand, Frédéric (McGill-Queen's native and northern series, 2010)
Annotation, While the transition to Christianity in the Canadian Arctic occurred between the end of the eighteenth century and the 1950s, the various and complex transformations that happened during this time have not been fully understood. Using both archival material and oral testimony collected during workshops in Nunavut between 1996 and 2008, FrÉdÉric Laugrand and Jarich Oosten provide a nuanced look at Inuit religion, offering a strong counter narrative to the idea that traditional Inuit culture declined post-contact. They show that setting up a dichotomy between a past identified with traditional culture and a present involving Christianity obscures the continuity and dynamics of Inuit society, which has long borrowed and adapted "outside" elements. They argue that both Shamanism and Christianity are continually changing in the Arctic and ideas of transformation and transition are necessary to understand both how the hunting ideology shaped Inuit Christian cosmology and how Christianity changed Inuit shamanic traditions. Inuit Shamanism and Christianityis particularly useful in distinguishing between the influence of Anglican, Catholic, and, more recently, Pentecostal and Evangelical movements and in delineating the ways in which Shamanism still influences modern life in Inuit communities